Desenvolvimento de um sistema giratório para carrocerias veiculares - Leite, Andrew Muliterno (2025)
The classic car restoration market in Brazil has been expanding over the last decade, driven by the appreciation of classic vehicles as investment assets and the growing search for historical preservation, nostalgia, and personalization. According to a survey by JDA Research for the International Federation of Vintage Vehicles (FIVA), in 2020/2021 the classic car market generated R$ 16.1 billion in direct spending; R$ 12.3 billion in the purchase and sale of historic vehicles; R$ 3.5 billion in historic vehicle events; and R$ 768 million in indirect spending, totaling a global market of R$ 32.6 billion per year. With the increase in demand for workshops specializing in high-standard automotive restoration, there is a need for qualified labor and also for equipment and tools that assist the restoration professional in performing their work with greater speed, quality, and safety. This work aimed to develop equipment that allows the body of a vehicle to rotate 360 ​​degrees, which is fundamental in restoration and preparation processes of bodies and chassis, ensuring easy access to all parts of the vehicle. A product development methodology was used, consisting of planning, concept, design and detailing. The results obtained from the study are the development of the complete equipment design, detailing and bill of materials, presentation of its operation, structural analysis by finite elements and cost evaluation.